Players of Th-cell differentiation and immune dysregulation – focus on GIMAP family genes - Heinonen, Mirkka (Annales Universitatis Turkuensis D 1183, 2015)
The balance of T helper (Th) cell differentiation is the fundamental process that ensures that the immune system functions correctly and effectively. The differentiation is a fine tuned event, the outcome of which is driven by activation of the T-cell in response to recognition of the specific antigen presented. The co-stimulatory signals from the surrounding cytokine milieu help to determine the outcome. An impairment in the differentiation processes may lead to an imbalance in immune responses and lead to immune-mediated pathologies. An over-representation of Th1 type cytokine producing cells leads to tissue-specific inflammation and autoimmunity, and excessive Th2 response is causative for atopy, asthma and allergy. The major factors of Th-cell differentiation and in the related disease mechanisms have been extensively studied, but the fine tuning of these processes by the other factors cannot be discarded. In the work presented in this thesis, the association of T-cell receptor costimulatory molecules CTLA4 and ICOS with autoimmune diabetes were studied. The underlying aspect of the study was to explore the polymorphism in these genes with the different disease rates observed in two geographically close populations. The main focus of this thesis was set on a GTPase of the immunity associated protein (GIMAP) family of small GTPases. GIMAP genes and proteins are differentially regulated during human Th-cell differentiation and have been linked to immune-mediated disorders. GIMAP4 is believed to contribute to the immunological balance via its role in T-cell survival. To elucidate the function of GIMAP4 and GIMAP5 and their role in human immunity, a study combining genetic association in different immunological diseases and complementing functional analyses was conducted. The study revealed interesting connections with the high susceptibility risk genes. In addition, the role of GIMAP4 during Th1-cell differentiation was investigated. A novel function of GIMAP4 in relation to cytokine secretion was discovered. Further assessment of GIMAP4 and GIMAP5 effect for the transcriptomic profile of differentiating Th1-cells revealed new insights for GIMAP4 and GIMAP5 function.

T-auttaja(Th)solujen erilaistuminen on avainasemassa immuunijärjestelmän tehokkaan toiminnan kannalta. Erilaistumisprosessi on tarkasti säädelty. Prosessia ohjaavat antigeeniä esittelevät solut, Th-soluja aktivoivat molekyylit sekä Th-solua ympäröivät sytokiinit. Prosessin häiriintymisestä voi seurata Th-solujen alaluokkien epätasapaino ja immunologinen epäjärjestys. Liiallinen Th1-solu vaste johtaa autoimmunisairauksiin ja liiallinen Th2-solu vaste aiheuttaa kroonisia tulehduksia; atopiaa, astmaa ja allergiaa. Vaikka Th-solujen erilaistumiseen vaikuttavia päätekijöitä ja mekanismeja on tutkittu paljon, immuunivasteen hienosäätelyyn vaikuttavat tekijä ja mekanismit ovat vielä laajalti selvittämättä. Tässä tutkimuksessa on selvitetty yhdessä T-solureseptorin kanssa Th-solu aktivaatioon tarvittavien, CTLA4 ja ICOS, molekyylien yhteys tyypin 1 diabetekseen kahdessa eri maantieteellisesti läheisessä populaatiossa, joissa sairauden esiintyvyys on hyvin erilainen. Tutkimuksen pääpaino on keskittynyt GIMAP eli Immuniteettiin assosioituneet proteiinit -perheen pienten GTPaasien toimintaan. GIMAP geenejä ja proteiineja säädellään eri tavoin ihmisen Th-solujen erilaistumisen aikana ja GIMAP perheen geenejä on yhdistetty immuunivälitteisiin sairauksiin eläinmalleissa. GIMAP4:n on osoitettu vaikuttavan Th-solujen solukuolemaan eli apoptoosiin ja GIMAP5:n on osoitettu olevan yhteydessä rotan ja hiiren autoimmuunihäiriöihin. Väitöskirjatyössä GIMAP4:n ja GIMAP5:n roolia Th-solujen erilaistumisessa ja immuniteetin häiriötiloissa selvitettiin yhdistämällä populaatiogeneettinen tutkimus toiminnallisen tutkimuksen kanssa. Selvitimme GIMAP4:n assosioituvan astmaan ja allergiaan, sekä GIMAP5 assosioituvan astmaan ja allergiaan, sekä tyypin 1 diabetekseen. Tutkimme lisäksi kyseisten GIMAP geenien välistä yhteisvaikutusta muiden tunnettujen tyypin 1 diabetekseen vaikuttavien tekijöiden kanssa. Lisäksi, havaitsimme GIMAP4:n vaikuttavan Th-solujen sytokiinien tuottoon varhaisen Th-solu erilaistumisen aikana sekä löysimme uusia seikkoja GIMAP4:n ja GIMAP5:n toiminnasta Th1-solun transkriptomin tasolla.